Outcome of Bacteremia and Fungemia in Pediatric Oncology Patients - Joan L Robinson; Robert P Rennie (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the outcome of paediatric oncology patients with positive blood cultures.>